Disruptive Innovation (DI) and Chief Executive Officer(CEO): A synthetic literature review - Chen Fu; Logaiswari Indiran; Umar Haiyat Abdul Kohar (International Journal of Business and Social Science Research, 2023)
Objective: This paper reviews the findings of empirical studies linking disruptive innovations directly or indirectly to CEOs for the period 2019-2023. It also explores disruptive innovation and the fuzzy concepts of CEO and CEO power and proposes future research directions. Research Design & Methods: Research methods are based on comprehensive literature reviews. In a three-step process, relevant papers are identified and categorized. These samples are then analyzed and brought into perspective to explain the concept of disruptive innovation and CEO, based on which recommendations for future research are made. Findings: Although many studies imply a correlation between disruptive innovation and CEOs, there are no empirical studies specifically addressing this link. The main reason seems to be a lack of clarity about the concept of "CEO" itself. Contribution & Value Added: This study introduces the concept of disruptive innovation based on the study of existing literature. Furthermore, it is an excellent starting point for scholars interested in clarifying disruptive innovation or preventing the discovery of the nature of the relationship between disruptive innovation and the CEO.